The relationship between customer-related social stressors and job outcomes: the mediating role of emotional exhaustion - Karatepe, Osman M.; Nkendong, Rita Anumbose (Routledge Journals, Taylor & Francis Ltd, 2014)
Using the health impairment process of the Job Demands-Resources (JD-R) model as the theoretical framework, this study proposes and tests a research model that investigates the mediating role of emotional exhaustion in the relationship between customer-related social stressors and job outcomes. Job performance, extra-role customer service, and turnover intentions are three job outcomes used in the current study. Respondents were full-time frontline hotel employees in Cameroon. Data were obtained from these employees with a time lag of one month. The results of structural equation modelling (SEM) suggest that emotional exhaustion fully mediates the relationship between customer-related social stressors, as manifested by disproportionate customer expectations (DCE), customer verbal aggression (CVA), disliked customers (DC), and ambiguous customer expectations (ACE), and the aforementioned job outcomes. Specifically, the results suggest that the indicators of customer-related social stressors jointly affect emotional exhaustion that, in turn, leads to negative job outcomes such as poor job performance, reduced extra-role customer service, and increased turnover intentions.
Keywords: Cameroon; customer-related social stressors; emotional exhaustion; frontline hotel employees; job outcomes